COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE IN PT. BANK RAKYAT INDONESIA (PERSERO) Tbk AND PT. BANK MANDIRI (PERSERO) Tbk, 2015-2019 PERIOD REGISTERED IN INDONESIA STOCK EXCHANGE: ANALISIS KOMPARATIF KINERJA KEUANGAN PT. BANK RAKYAT INDONESIA (PERSERO) Tbk DAN PT. BANK MANDIRI (PERSERO) Tbk PERIODE 2015-2019 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ombi Romli; Suflani Suflani; Luvita Santi (Yayasan Education and Social Center, 2021)
The ability of financial institutions to maintain their credibility shows the condition of an institution at a particular time or period, whether in scope as a public fund collector or otherwise channeling funds to the public. To measure the performance of a financial institution through financial ratio analysis is generally used to measure the financial performance of all companies, both private and state-owned companies, namely the ratio of liquidity, solvency, and profitability. This research aims to find out and analyze how big the comparison is between the financial performance of a conventional bank, namely Bank Rakyat Indonesia Tbk, and the conventional bank Bank Mandiri Tbk which has been listed on the Indonesian stock exchange or abbreviated (BEI). This research data used by researchers are using secondary data, where the method used is a descriptive analysis method of case studies is through solving a case using financial reports in assessing a financial performance at financial institutions Bank Rakyat Indonesia (Persero) Tbk and Bank Mandiri (Persero) ) Tbk. From 2015-2019. Based on the analysis of financial performance for 2015-2019 at BRI and Mandiri, which is seen from the Profitability Ratio using ROA, ROE, NPM, it is found that BRI bank in the 2015-2019 period was better than independent banks. Based on the 2015-2019 financial performance analysis at BRI and Mandiri, as seen from the Solvency Ratio using DER and DAR, it was found that BRI bank in the 2015-2019 period was better than Bank Mandiri. From the research analysis, it can be concluded that the management of Bank Mandiri would be better off to continue to pay attention to and increase financial performance and productivity in the institution. In contrast, the management of Bank BRI, even though it has been declared good, needs to continue to improve the quality of its institutional financial performance in a transparent and accountable manner